Piotr Skarga tłumaczem nowoczesnym? Polski i angielski przekład Rationes decem Edmunda Campiona — próba porównania - Calma, Clarinda (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article discusses preliminary results of a comparative analysis of two translations of Edmund Campion’s (1540–1581) Rationes decem. One being the Polish translation entitled Dziesięć wywodów by Piotr Skarga (Wilno, 1584) and the other being the English translation of an unknown translator (Rouen 1632). The article begins with a brief historical outline of the genesis of Campion’s work and compares the two translations in the light of the “translator’s invisibility” theory formulated by Lawrence Venuti. Selected passages from both translations are then analyzed in accordance with Edward Balcerzan’s typology of textual transformations in translation. Skarga’s translation, in comparison with the later English translation, seems to be closer to the original text. The most common type of transformation applied in the Polish text is inversion and complementation (adiectio), whilst in the English translation predominant translation strategies are substitution and complementation. Skarga as the ‘invisible’ translator faithfully renders the original text, and his editorial decisions encourage the reader to become an independent reader. The article presents preliminary results of a research project on the study of subversive publications in sixteenth-century England and their reception in the Republic of Poland-Lithuania. The Project is funded by the Polish National Science Centre.